2021
DOI: 10.3390/pathogens10121647
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Anatomopathological Evaluation of BALB/c Murine Models Infected with Isolates of Seven Pathogenic Sporothrix Species

Abstract: Background: Sporotrichosis is a subcutaneous mycosis with worldwide distribution and caused by seven pathogenic species of Sporothrix genus: S. schenckii sensu stricto, S. brasiliensis, S. globosa and S. luriei (clinical clade), and the species S. mexicana, S. pallida and S. chilensis (environmental clade). Isolates of the same species of Sporothrix may have different pathogenicities; however, few isolates of this fungus have been studied. Thus, the aim of this work was to analyze the clinical and anatomopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…Gandra and colleagues [31] observed that by inoculating 1x10 7 Candida albicans/larvae, CFUs ranged from 1.0x10 8 to 1.0x10 12 at 6, 24, and 48 hours. These data reinforce the suitability of G. mellonella as a model of yeast infection since it differentially mirrors Candida and Sporothrix fungal loads increase, such as previously described for mammalian hosts [47,48].…”
Section: Discussionsupporting
confidence: 86%
“…Gandra and colleagues [31] observed that by inoculating 1x10 7 Candida albicans/larvae, CFUs ranged from 1.0x10 8 to 1.0x10 12 at 6, 24, and 48 hours. These data reinforce the suitability of G. mellonella as a model of yeast infection since it differentially mirrors Candida and Sporothrix fungal loads increase, such as previously described for mammalian hosts [47,48].…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, another study found a more pronounced proinflammatory profile induced by S. brasiliensis in human PBMCs in comparison to S. schenckii [ 56 ], suggesting that factors within the same species can impact their behavior upon interaction with the host. The study by Corrêa-Moreira et al [ 57 ] indicates that virulence may be related to the isolate independent of the Sporothrix species. Sporothrix virulence characteristics have not been assessed in the causative isolates from this study, but it is safe to say that evasion mechanisms of the fungus may interfere with the capacity of the feline host to cope with the infection, and it is possible that the impaired phagocytosis in cats with sporotrichosis may be related to more pathogenic isolates of Sporothrix .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis was performed following the protocols described by Corrêa-Moreira et al [19]. At each point of observation (21,35 and 49 days after inoculation), clinical signs were observed such as cutaneous lesions, alopecia and apathy in the mice.…”
Section: Infection Capacity Of the Isolatesmentioning
confidence: 99%